(untitled) - International Conference on Computational Methods in Water Resources (Boston, 2004)
The XV International Conference on Computational Methods in Water Resources (CMWR XV) was held in Chapel Hill, North Carolina, 13-17 June 2004. The conference was sponsored by the Department of Environmental Sciences and Engineering, School of Public Health, The University of North Carolina at Chapel Hill. This two-volume set represents the reviewed and edited proceedings of this meeting, including 156 papers. In addition, many posters were presented at the meeting, which are not included in this formal written record.
Keywords: Hydrology,Hydrology,Groundwater,Groundwater flow,Thủy học,Nước ngầm,Mạch nước ngầm; Data processing,Mathematical models,Data processing,Data processing,Mô hình toán học,Xử lý dữ liệu,Xử lý dữ liệu